Keberadaan Majelis Tafsir Al-Qur’an dalam Pandangan Masyarakat Kecamatan Pamatang Sidamanik - Tri Andriansyah; Kamaluddin Kamaluddin (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2024)
This research is qualitative research that aims to determine the community's response to the existence of the Al-Qur'an Tafsir Council (MTA) Pamatang Sidamanik Branch in Sinaman II Village. Collecting data using the method of observation, documentation and interviews. The research data was analyzed using a descriptive analysis method. The results of the study show that the existence of MTA reaps the pros and cons of the community. The existence of MTA makes it easier for pilgrims to understand Islamic teachings in depth by referring to the Qur'an and Sunnah. Meanwhile, the response from the community outside the MTA congregation was quite diverse. Some of them appreciate it, others are neutral and even reject it. This is due to several factors, including ideological factors, educational background and personality.